PENGEMBANGAN APLIKASI POWTOON DALAM PEMBELAJARAN HYBRID LEARNING - Fuadah Amran, Hasanatul; Farianti Amran, Husna; K, Hendri (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2023)
In the era of digitalization 5.0, learning can not only be done face-to-face, the hybrid learning method allows learning to be carried out without knowing distance and time. Hybrid combines or mixes face to face learning and computer-based learning (online and offline). The learning process can be designed by adjusting to the needs. Learning design aims to increase the efficiency and effectiveness of a learning system. One of the web-based learning models is to use powtoon as a medium. Powtoon is one of the freeware or programs that are used for free by internet users and not many have developed learning media with Powtoon. Several studies have shown that Powtoon can improve the quality of the teaching and learning process, the material presented using the Powtoon application becomes clearer and real and students become easier to understand the material. The purpose of this study is to develop the Powtoon application in hybrid learning learning. This research is a development research using a mixed method The design and approach used in this research is the development of Research & Development (R&D). In the development of this learning video, a model is used. 4D (Four D) development. This research was carried out at SMK Muhammadiyah 3 Pekanbaru, in the even semester of the 2021/2022 academic year. The research population is productive teachers of TKJ SMK Muhammadiyah 3 Pekanbaru and students of class X TKJ 2 SMK Muhammadiyah 3 Pekanbaru. With a sample of 2 productive TKJ teachers and 15 students of class X TKJ 2, which were taken by purposive sampling techniques. The products and instruments developed are: Powtoon animation learning videos and student ability test questions. The results showed that experimental classes that had used Powtoon learning videos had better learning abilities than t test control classes (0.02 < 0.05). It was concluded that the Powtoon learning videos developed were effective in improving students' learning abilities.